ACTOVEGIN INFLUENCE ON METABOLIC AND VASOMOTOR FUNCTION OF MICROVASCULAR ENDOTHELIAL OF HUMAN SKIN - A. A. Fedorovich; A. N. Rogoza; E. M. Kanisheva; S. A. Boytsov (Столичная издательская компания, 2016)
Aim. To evaluate effects of Actovegin (deproteinized hemoderivative) on vasomotor and metabolic functions of microvascular skin endothelium in healthy volunteers during acute pharmacological test.Material and methods. 24 healthy male volunteers, aged 18-26 years (21,9±2,7), received Actovegin i.v. during 2 hour infusion through the left cubital vein. Right forearm skin laser Doppler flowmetry (LDF) with wavelet analysis of the microcirculatory oscillations was used initially and after 2 hour Actovegin infusion to assess microvascular endothelial responses (microcirculatory blood flow changes) to Actovegin. Saline infusion in 5 subjects used for control data receiving.Results. Actovegin significantly increased in maximal amplitude endothelial rhythm (at a frequency of 0.01 Hz) by 76% (p<0,001) and functional contribution of microvascular endothelium in the overall level of tissue perfusion by 79% (p<0,001). Control saline infusion resulted in reduction of these indices by 52 and 54%, respectively. Actovegin also increased significantly myogenic rhythm amplitude (vascular tone reduction) by 35% (p<0,05) and decreased diastolic blood pressure by 3 mm Hg (p=0,076), which is likely result of increased endothelium nitric oxide release.Conclusion. Microcirculatory oscillations at the frequency of 0.01 Hz reflect both vasomotor and metabolic function of microvascular endothelium. Actovegin improves oxygen and glucose tissue utilization as well as increases nitric oxide production with microvascular smooth muscle tone reduction.